The impact of regulatory compliance behavior on hazardous waste generation in European private healthcare facilities - Botelho, Anabela (2013)
Along with the increased provision of healthcare by private outpatient healthcare facilities within the EU countries, there is also an increase on waste generation from these facilities. A significant fraction of this waste is amongst the most hazardous of all wastes arising in communities, posing significant risks to people and the environment if inappropriately managed. The growing awareness that mismanagement of healthcare waste has serious environmental and public health consequences is reflected in the European waste legislation, aiming at waste prevention at the source and emphasizing the “management” aspects of the waste management process. Whether the increasingly large numbers of private healthcare facilities comply with the existing European waste legislation, and whether compliance with such legislation affects the fraction of healthcare waste classified as hazardous is an understudied subject. Using a large survey of private outpatient healthcare facilities, this study finds that although compliance with the law is far from ideal, it is the strongest factor influencing hazardous waste generation. These findings suggest that more public investments in monitoring healthcare facilities’ compliance with the law in EU countries is warranted, along with increased efforts to raise the facilities’ awareness of the cost savings brought about by compliance with the existing healthcare waste legislation.